Solvated adhesive composition and method
Patent Information
- Application Number
- JP2024123442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2024-07-30
- Publication Date
- 2025-02-26
Smart Images

Figure 2025026825000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 63 / 517,017, filed Aug. 1, 2023, which is incorporated by reference herein in its entirety. [Background technology]
[0002] Currently, golf club grips are attached using a method that includes a solvent (e.g., an aliphatic solvent) and a solid double-sided tape. The tape is first applied (wrapped) around the golf shaft at the location where the grip will be attached. A solvent is then applied onto the surface of the tape to lubricate the surface and allow the grip to slide onto the shaft (reducing friction) over the adhesive tape. When a user wants to remove the grip and attach a second grip, the grip is removed from the tape and shaft (usually by cutting the grip). When the grip is removed, the tape remains on the golf shaft. Before additional tape and a second grip can be applied, the tape must be removed. This tape removal is tedious, involves time consuming steps, and can damage the shaft material if done improperly, such as heating, cutting, and / or scraping. Summary of the Invention
[0003] Disclosed herein is the use of a solvated adhesive / tackifier composition as a stabilizing medium for, for example, attachment and fastening of a golf club grip. The disclosed composition may be applied onto the inner shaft-facing surface of a golf grip. When the grip is to be attached to the shaft, a solvent is applied to the shaft. The liquid solvating composition provides lubrication for sliding the golf grip on the golf club shaft, and the solvent may solvate the adhesive composition. The grip / shaft is left to dry at room temperature for a period of time, after which the same composition acts as an adhesive / tackifier to secure the grip to the shaft and prevent slipping or rotation of the grip on the shaft.
[0004] This summary is provided to introduce some concepts in a simplified form that are more fully described in the detailed description. This summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used to limit the scope of the claimed subject matter. [Brief description of the drawings]
[0005] Non-limiting and non-exhaustive examples are described with reference to the following figures.
[0006] [Figure 1] FIG. 1 shows a side view of a grip attached to the end of a golf club shaft, according to an embodiment.
[0007] [Diagram 2] FIG. 2 shows an exploded perspective view of the grip and shaft end of FIG. 1 according to an embodiment.
[0008] [Diagram 3] FIG. 3 illustrates a cross-sectional view of the grip of FIG. 1, according to an embodiment.
[0009] [Figure 4] FIG. 4 illustrates a method of coating a grip with an adhesive composition, according to an embodiment.
[0010] [Diagram 5] FIG. 5 illustrates a method of attaching a grip containing an adhesive composition to a shaft, according to an embodiment.
[0011] [Figure 6] FIG. 6 shows torque test data for various grip formulations and compositions after 16 hours of curing, according to the examples.
[0012] [Figure 7] FIG. 7 shows torque test data for various grip formulations and compositions after 24 hours of humidity aging, according to the examples.
[0013] [Figure 8] FIG. 8 shows torque test data for various grip formulations and compositions including at least polyisobutylene, according to the examples.
[0014] [Figure 9] FIG. 9 illustrates adhesion testing data for various grip formulations and compositions including at least polyisobutylene, according to examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Detailed Description In the following detailed description, reference is made to the accompanying drawings, which form a part of this specification and which show by way of illustration certain embodiments or examples. These aspects may be combined, other aspects may be utilized, and structural changes may be made without departing from the present disclosure. The examples may be implemented as a method, a system, or an apparatus. It is to be understood that the present invention is not limited to the specific methodology, protocols, and reagents, etc. described herein, as such may vary. Therefore, the following detailed description is not to be taken in a limiting sense, and the scope of the present disclosure is defined by the appended claims and their equivalents.
[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood to one of ordinary skill in the art to which this invention pertains.
[0017] For purposes of this application, the following terms shall have the following meanings.
[0018] As used in this specification and claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise.
[0019] All numbers expressing quantities of ingredients or reaction conditions used herein, except in the examples or where otherwise indicated, should be understood to be modified in all instances by the term "about." The term "about" is used herein in connection with numerical values to mean ±20% and in connection with percentages to mean ±4%.
[0020] As used herein, the term "comprising" is inclusive and refers to a composition, compound, formulation, or method that does not exclude additional elements or method steps.
[0021] As used herein, the term "consisting of" refers to a compound, composition, formulation, or method that excludes the presence of any additional ingredient or method step.
[0022] As used herein, the term "consisting essentially of" refers to a composition, compound, formulation, or method that includes additional elements or process steps that do not materially affect the characteristics of the composition, compound, formulation, or method.
[0023] As used herein, the solvating adhesive / tackifier is used as a stabilizing medium for, for example, attaching and fastening a golf club grip or other similar object (e.g., a hockey stick, lacrosse stick, fishing rod, hand tool, or other suitable shaft having a grip attached thereto). Use of the composition is disclosed. The disclosed composition can be applied to the inner shaft-facing surface of the grip. This application can occur during or after the grip manufacturing process. The composition can be allowed to dry on the grip, and the grip can then be provided to a user. In some examples, the grip containing the composition is provided to the user in a kit that also includes a suitable solvent.
[0024] When the grip is attached to the shaft, a solvent is applied to the shaft. The liquid solvating composition provides lubrication for sliding the golf grip on the golf club shaft, and the solvent may solvate the adhesive composition. The grip / shaft is left for a period of time (in some instances, at room temperature) until the solvated composition dries, and the same composition, once dry, acts as an adhesive / tackifier to secure the grip to the shaft and prevent longitudinal sliding and / or rotation of the grip on the shaft.
[0025] In some examples, the disclosed compositions can be applied to a grip, and the grip having the dried adhesive composition film can be provided to and / or used by a consumer. In some examples, the grip having the dried adhesive composition film can be provided to a consumer as a kit along with an appropriate amount of a lubricating solvent. For example, a package can include a grip having a dried adhesive composition film on its inner surface.
[0026] 1 shows a side view of an assembly 10 including a grip 18 attached to the end of a shaft 16 of a golf club 12. The golf club 12 has a head 14 at a first end of the shaft 16. At a second end of the shaft 16 (distal end 32, see FIG. 2 ), a grip 18 is attached to an exterior surface 30 of the shaft 16.
[0027] FIG. 2 shows an exploded perspective view of the grip 18 and the distal end 32 of the shaft 16. In some examples, the shaft 16 is circular in cross section and cylindrical in shape, with its length extending along an axis X. In some examples, other shapes and cross sections are possible. The grip 18 is configured to fit (e.g., slide) over the outer surface 30 of the distal end 32 of the shaft 16 such that the distal end 32 of the shaft 16 is inserted into the open end 20 of the grip 18. The open end 20 and inner surface 26 (see FIG. 3) of the grip may be circular in cross section and concentric with the outer surface 30 along the axis X. In some examples, other shapes and cross sections are possible. The grip 18 has a closed end 22 opposite the open end 20. In some examples, when the grip 18 is fully attached / mounted on the shaft 16, the inner surface 40 (see FIG. 3) of the closed end 22 contacts the end of the distal end 32.
[0028] 3 is a cross-sectional view of grip 18. In some examples, closed end 22 includes holes, perforations, or other openings that allow air to pass through closed end 22 (and through the inner surface of closed end 22) when grip 18 is slid onto shaft 16.
[0029] The inner surface 26 may be of the same shape as the distal end 32 of the shaft 16. The inner grip 18 defines an interior volume 28 having a side defined by the inner surface 26, a first end defined by the inner surface 40 of the closed end 22, and a second end defined by the open end 20. The interior volume 28 receives the distal end 32 of the shaft 16 when the grip 18 is attached / mounted to the shaft 16. The grip 18 has an outer surface 24 (which a user can grasp during use of the assembly 10). The outer surface 24 may be configured such that the thickness of the material of the grip 18 is uniform throughout the grip 18. In other examples, the outer surface 24 may be configured such that the thickness of the material of the grip 18 is non-uniform throughout the grip 18 (e.g., the thickness is greater toward the closed end 22 and less toward the open end 20, as shown in FIG. 3).
[0030] In some examples, grip 18 may include materials such as rubber, vulcanized rubber (e.g., elastomeric vulcanized rubber, etc.), natural or synthetic polymers (e.g., polyurethane, ethylene-vinyl acetate, etc.), leather, leather-based compositions, other suitable materials, or combinations thereof. In some examples, other materials or combinations of materials are contemplated. In some examples, grip 18 is flexible.
[0031] A film or coating 34 of an adhesive composition may be applied to the inner surface 26 of the grip 18. In some instances, the adhesive composition may be significantly tacky or sticky to the touch. The adhesive composition may, in some instances, be activated by contact with a solvent. A lubricating solvent may be applied to the coating 34 on the inner surface 26 and / or the distal end 32 of the shaft 16.
[0032] The adhesive composition, in some examples, may be applied by spraying, rubbing, pouring, brushing, or other suitable automated or manual application methods. In some examples where the adhesive composition is applied by hand, the adhesive composition may be applied to the inside of the grip by dripping about 2 milliliters (mL) of the adhesive composition into the interior volume of the grip, covering the open end of the grip, and shaking the grip until the inner surface of the grip is coated with the adhesive composition.
[0033] In some examples, the amount of adhesive composition applied to inner surface 26 is about 2 mL. In some examples, the amount of adhesive composition applied to inner surface 26 is between 1 mL and 3 mL. In some examples, the amount of adhesive composition applied to inner surface 26 is between 0.5 mL and 5 mL. In some examples, the amount of adhesive composition applied to inner surface 26 is between 1 mL and 2 mL. In some examples, the amount of adhesive composition applied to inner surface 26 is between 2 mL and 3 mL. In some examples, the amount of adhesive composition applied to inner surface 26 is at least 2 mL.
[0034] In some examples, the adhesive composition is dried for 24 hours. In some examples, the adhesive composition is dried for 48 hours. In some examples, the adhesive composition is dried for 36 hours. In some examples, the adhesive composition is dried for 72 hours. In some examples, the adhesive composition is dried for at least 24 hours. In some examples, the adhesive composition is dried for 24 to 48 hours. In some examples, the adhesive composition is dried for 12 to 24 hours. In some examples, the adhesive composition is dried for 24 to 72 hours. In some examples, the adhesive composition is dried at room temperature and ambient humidity conditions.
[0035] In some examples, the adhesive composition dry film 34 may have a dry film thickness of about 1 micron to 40 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness of about 1 micron to 20 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness of about 20 microns to 40 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness of about 10 microns to 30 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness of about 1 micron to 60 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness of about 20 microns to 60 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness greater than 20 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness greater than 5 microns. In some examples, the adhesive composition dry film 34 may have a dry film thickness greater than 40 microns. In some examples, the dry film 34 of the adhesive composition may have a dry film thickness of less than 40 microns. In some examples, the dry film 34 of the adhesive composition may have a dry film thickness of less than 20 microns.
[0036] In some examples, the lubricating solvent is applied to the dried adhesive composition film 34 and / or the distal end 32 of the shaft 16 by spraying, wiping, pouring, brushing, or other suitable manual or automated methods. In some examples where the solvent is applied manually, it may be applied by a bottle with a nozzle in an amount of 2-20 mL. In some examples, the amount of solvent applied may be less than 20 mL. In some examples, the amount of solvent applied may be more than 2 mL. In some examples, the amount of solvent applied may be more than 20 mL. In some examples, the amount of solvent applied may be 2 mL-20 mL. In some examples, the amount of solvent applied may be 2 mL-10 mL. In some examples, the amount of solvent applied may be 10 mL-20 mL. In some examples, the amount of solvent applied may be 5 mL-15 mL. In some examples, the amount of solvent applied may be about 10 mL.
[0037] In some examples, the lubricating solvent provides lubrication for sliding the inner surface 26 of the grip 18 over the distal end 32 of the shaft 16. In some examples, the lubricating solvent at least partially solvates the adhesive composition upon contact, and the solvated adhesive composition provides lubrication for sliding the inner surface 26 of the grip 18 over the distal end 32 of the shaft 16. In some examples, both the lubricating solvent and the solvated adhesive composition may provide lubrication for sliding the inner surface 26 of the grip 18 over the distal end 32 of the shaft 16.
[0038] Once the grips 18 are mounted on the shaft 16, they are allowed to dry so that the grips 18 can properly adhere to the shaft 16. In some instances, the mounted grips are allowed to dry for 16 hours. In some instances, the mounted grips are allowed to dry for 24 hours. In some instances, the mounted grips are allowed to dry for 48 hours. In some instances, the mounted grips are allowed to dry for 36 hours. In some instances, the mounted grips are allowed to dry for 72 hours. In some instances, the mounted grips are allowed to dry for at least 12 hours. In some instances, the mounted grips are allowed to dry for at least 16 hours. In some instances, the mounted grips are allowed to dry for at least 24 hours. In some instances, the mounted grips are allowed to dry for 16-24 hours. In some instances, the mounted grips are allowed to dry for 24-48 hours. In some instances, the mounted grips are allowed to dry for 12-24 hours. In some instances, the mounted grips are allowed to dry for 24-72 hours. In some instances, the mounted grips are allowed to dry at room temperature and ambient humidity conditions. In some instances, the installed grips are dried by humidity aging, for example at 95% relative humidity and 32°C.
[0039] In some examples, the adhesive composition is prepared by dissolving one or more tackifier components in one or more solvents. In some examples, the solvent includes mineral spirits. In other examples, other suitable solvents may be used. In some examples, the suitable solvent may include toluene, benzene, xylene, petroleum naphtha, isopentane, nonane, petroleum distillates, mineral spirits, another suitable solvent, or a combination thereof. In some examples, the solvent used is non-aqueous. In some examples, the tackifier components are insoluble in water. In some examples, the tackifier components do not readily dissolve in water. In other examples, the solvent is water or an aqueous solvent. In such examples, the tackifier components may be soluble in water.
[0040] In some examples, the tackifier component is a liquid. In other examples, the tackifier component is a solid. In some examples, the tackifier component is a resin (e.g., a hydrocarbon resin (such as an aliphatic resin), a terpene resin, a rosin resin, etc.), an epoxy, an acrylic adhesive, a silicone adhesive, a plastic adhesive, a rubber adhesive, a urethane adhesive, or the like. or other adhesive / tackifier types or combinations thereof. In some examples, the tackifier component may include a hydrocarbon resin, such as an aliphatic resin (e.g., C5 resin), an aromatic resin, a monomer, or a combination thereof. In some examples, suitable aliphatic (C5) resins may include cis / trans 1,3-pentadiene, 2-methyl-2-butene, cyclopentene, cyclopentadiene, and dicyclopentadiene, or other suitable resins or combinations thereof. In some examples, suitable aromatic (C9) resins may include those having base monomers of indene, methylindene, dicyclopentadiene, styrene, α-methylstyrene, vinyl toluene, other suitable monomers, and combinations thereof. In some examples, suitable polyisobutylene (which may be referred to as polyisobutene or PIB) may be prepared via a polymerization reaction of isobutene and may have a chemical formula of (C4H8)n. In some examples, suitable alkylphenol resins may be prepared via a condensation reaction of an aldehyde with an alkylphenol. In some examples, the tackifier component may include a C5 resin, a polyisobutylene, an alkylphenol (alkylphenol) resin, or a combination thereof.
[0041] In some examples, the total amount of tackifier components (including one or more tackifier components) may be present in the wet adhesive composition in an amount of about 10 parts by weight (e.g., grams (g)) per about 100 parts by weight of solvent (e.g., mineral spirits). In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount of about 12.5 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount of about 15 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount of about 20 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 2.5 parts by weight and about 5 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 2.5 parts by weight and about 10 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 5 parts by weight and about 10 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 5 parts by weight and about 15 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 10 parts by weight and about 15 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 10 parts by weight and about 15 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 10 parts by weight and about 20 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount between about 2.5 parts by weight and about 20 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount less than 2.5 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount greater than 10 parts by weight per about 100 parts by weight of solvent. In some examples, the total amount of tackifier components may be present in the wet adhesive composition in an amount greater than 20 parts by weight per about 100 parts by weight of solvent.
[0042] In some examples, when two tackifier components are present in the adhesive composition, they may be present in a ratio of 2.5:10, 5:10 (1:2), or 10:10 (1:1).
[0043] In some instances, a suitable lubricating solvent (e.g., a solvent that is applied to the dry film on the distal end of the grip or golf shaft prior to attaching the grip to the shaft) may include a non-aqueous solvent. In other instances, the lubricating solvent may be an aqueous solvent. In some instances, the solvent may be mineral spirits, water, acetone, naphtha, toluene, benzene, xylene, isopentane, nonane, petroleum distillates, isopropyl alcohol, another suitable solvent, or the like. It may include combinations of these.
[0044] Testing of the adhesive composition and / or lubricating solvent combination may include a torque test and a tack test (both of which are described further below with reference to the included examples). The torque test determines the amount of twist (i.e., rotational slip around the outer surface of the shaft) that the grip has with respect to the shaft when force is applied. In preferred examples, minimal slip is desired. The torque test result is measured in degrees of deflection. In some examples, a satisfactory angle is less than about 4.5 degrees. In some examples, a satisfactory angle is less than about 3 degrees. In some examples, a satisfactory angle is about 1.5 degrees. In some examples, a satisfactory angle is between 1 degree and 5 degrees. The tackiness test determines the tackiness (or "stikiness") of the surface and can be measured in units of force (e.g., gram force (gF)). In preferred examples, a higher tackiness test result is desired. In some examples, a satisfactory tackiness test result is greater than about 1,000 gF. In some examples, a satisfactory tackiness test result is greater than about 2,000 gF. In some instances, a satisfactory tack test result is greater than about 1,500 gF. In some instances, a satisfactory tack test result is greater than about 2,500 gF. In some instances, a satisfactory tack test result is greater than about 1000 gF. In some instances, a satisfactory tack test result is about 2,700 gF. In some instances, a satisfactory tack test result is between about 1,000 gF and about 4,000 gF. In some instances, a satisfactory tack test result is between about 2,000 gF and about 3,000 gF. In preferred instances, the dried adhesive composition may be noticeably sticky or viscous to the touch. In preferred instances, the dried adhesive composition forms a smooth film, is not cakey, is flexible, and does not crack or peel when the grip material is bent.
[0045] FIG. 4 illustrates an exemplary method 400 of coating a grip with an adhesive composition. In step 402, an adhesive composition may be prepared including obtaining a solvent (e.g., mineral spirits or another suitable solvent) and dissolving at least one adhesive (e.g., alkylphenol resin, C5 resin, and / or polyisobutylene) in the solvent. The adhesive may be a liquid or a solid, in various examples. In step 404, the adhesive composition is applied (e.g., by spraying, dripping, shaking, brushing, or another suitable method as described herein) onto the inner surface of the grip. In step 406, the adhesive composition is allowed to dry for a predetermined period of time.
[0046] FIG. 5 illustrates an exemplary method 500 for attaching a grip including an adhesive composition to a shaft. In step 502, a (lubricating) solvent (e.g., mineral spirits, water, naphtha, or acetone) is obtained and applied onto the outer surface of the end of the shaft. The end of the shaft may be opposite a second end of the shaft that includes a head, paddle, or other feature. The solvent may be applied by rubbing, brushing, dipping, spraying, or other suitable means as described herein. In step 504, the inner surface of the grip is slid onto the outer surface of the shaft, where the solvent and / or solvated adhesive composition acts as a lubricant on the shaft. In step 506, the solvent is dried and the adhesive composition adheres the grip onto the outer surface of the shaft.
[0047] In some instances, after use of the grip, it may be desired to remove the grip and replace it with another grip. In step 508, the grip may be capable of being removed from the shaft. For example, the grip may be pulled, twisted, peeled, cut, or otherwise removed from the shaft. In some instances, some residue of the adhesive composition remains on the shaft after the grip is removed. In other instances, no residue of the adhesive composition remains on the shaft after the grip is removed. In step 510, a second grip is obtained that includes the adhesive composition on an inner surface of the second grip. In step 512, a solvent is obtained and the solvent is removed. In step 514, the inner surface of a second grip is slid onto the outer surface of the shaft, where the solvent acts as a lubricant on the shaft. In step 516, the solvent is allowed to dry and the adhesive composition adheres the second grip onto the outer surface of the shaft.
[0048] In some examples, the disclosed compositions may be applied to a grip, and the grip with the dried adhesive composition film may be provided to a consumer and / or utilized. The grip may be provided alone in some examples. The grip may be provided already attached to a golf club or other shaft in some examples. The grip may be provided with a golf club or other shaft in some examples, but may not be attached (and in some examples, the solvent may be provided). In some examples, the grip with the dried adhesive composition film may be provided to a consumer as a kit, along with an appropriate amount of lubricating solvent. In some examples, the kit may also include a golf club or other suitable shaft. In some examples, the kit may include one or more droppers, brushes, and / or other suitable means for applying the solvent to a desired shaft. In some examples, the solvent included in the kit may be in a bottle, bag, dropper, syringe, or other suitable container. In some examples, the items included in the kit may be in a bag, box, vacuum sealed package, canister, package, blister package, molded package, or other suitable package or container. EXAMPLES
[0049] Working Example
[0050] Example 1
[0051] In Example 1, three different compositions were applied to a golf grip, a solvent was applied, the grip was attached to a test shaft, and the resulting adhesive grip was subjected to a torque test. Also tested were golf grips with no composition applied thereto (attached using solvent only) and golf grips using (double-sided) tape and solvent.
[0052] Torque testing is performed to determine the amount of twist (i.e., rotational movement) that the grip has relative to the shaft when force is applied. The test equipment used is an Auditor OPTOMETRIX Model RS-232 available from Auditor, Inc. (781 Sec. 4, Fenglin Road, Da Liao District, Kaohsiung City, Taiwan 83166, Taiwan). Golf grips were obtained and prepared for testing. The particular grip used in this example was a Tour Velvet 60R grip by EATON Golf Pride® available from Unit 1&2 Ltd. (The Stirling Centre, Northfields Road, Market Deeping, Peterborough, PE6 8EQ, United Kingdom). The grips were prepared according to Table 1 below. The adhesive compositions in this and other examples described herein are prepared by adding the recited parts by weight (in grams (g)) to 100 parts of liquid solvent. For example, the adhesive composition for Grip C was prepared by dissolving 10 g of C5 resin in 100 g of mineral spirits.
[0053] [Table 1]
[0054] Grip A was prepared by applying a solvent (mineral spirits) to the shaft, not taping the shaft, and not applying an adhesive composition on the inner surface of the grip. Grip B was prepared by applying a solvent (mineral spirits) to the shaft, taping the shaft, and not applying an adhesive composition on the inner surface of the grip. Grip C was prepared by first dissolving C5 resin in mineral spirits to form an adhesive composition, applying the adhesive composition on the inner surface of the grip, allowing the adhesive composition to dry, and then not taping the shaft and applying a solvent (mineral spirits) to the shaft. The C5 resin used was Wingtack 95 available from Zeon Chemicals (Thailand) Co., Ltd., 3 Soi Gee 14, Pakorn-Songkrorad Road, Tambon Houaiporn, Amphoe Muang Rayong, Rayong 21150, Thailand. Grip D was prepared in the same manner as Grip C, except that the adhesive composition was prepared by dissolving polyisobutylene in mineral spirits. The polyisobutylene used was HV-1900 available from ENEOS Corporation, 2-3-1 Yoko, Kawasaki-ku, Kawasaki City, 210-8545, Japan. Grip E was prepared in the same manner as Grip C and Grip D, except that the adhesive composition was prepared by dissolving alkylphenol resin in mineral spirits. The alkylphenol resin used was SP1068 available from SI Group, 1790 Hughes Landing Boulevard, The Woodlands, Texas 77380.
[0055] Solvent (for these and other prepared grips tested in the examples listed herein) was applied in an amount of 2-20 mL by a nozzle-equipped bottle to the area of the end of the shaft where the grip would be attached. Adhesive composition (for these and other prepared grips tested in the examples listed herein) was applied to the inside of the grip by dripping approximately 2 mL of adhesive composition into the interior volume of the grip, covering the open end of the grip, and shaking the grip until the inner surface of the grip was coated with the adhesive composition.
[0056] A steel torque test mandrel having the same diameter as a standard golf club shaft (0.6 inch diameter) was obtained for testing each prepared grip. Each of Grips A-E was mounted using mineral spirits. Exemplary mineral spirits are available from SolvChem, Inc. (Pearland, Texas 77581).
[0057] After each grip was attached / mounted onto the test mandrel, it was allowed to dry at room temperature for 16 hours to dry the applied composition and set the grips onto the test mandrel. The test mandrel with the grips attached was then placed onto the test fixture. To ensure that each grip tested was facing the same direction, each grip was mounted with the manufacturer's logo facing up. The shaft of the mandrel was clamped into place on the test fixture, and then the clamp force gauge and angle meter were activated. The force gauge clamp was then clamped to 40 kg / cm 2 The angle meter was then zeroed, the locking pin was pulled out, and the grip was twisted so that it was free to twist around the mandrel shaft. A 900g weight was added to the extended arm of the test fixture (the weight was added so that it would not move or swing). The weight on the arm A force of 0.05 applied a rotational torque to the mandrel shaft. Angle readings were recorded 15 seconds after the force was applied. The angle reading corresponds to the amount of deflection / rotation of the grips around the shaft. A smaller angle reading indicates less slippage / rotation of the grips around the shaft and is therefore desirable.
[0058] FIG. 6 shows the results of the angle (measured in degrees of deflection) data obtained from torque testing of the formulations in Table 1. The performance of Grip A represents the control baseline. In this example, Grip B performed above the baseline (i.e., experienced more slip / flex / rotation when torque was applied) and Grips C-E performed below the baseline (i.e., experienced less slip / flex / rotation when torque was applied). Also shown is the historical performance of a typical golf grip that was attached in a traditional manner using tape and solvent.
[0059] An observation made when working with different adhesive compositions was that the solid C5 resin dissolved surprisingly easily in mineral spirits. The polyisobutylene (liquid rubber) adhesive composition, when formulated into an adhesive composition / solution and applied to the grip, was surprisingly tacky to the touch.
[0060] Example 2
[0061] In Example 2, two different compositions were applied to golf grips, a solvent was applied, the grips were attached to test shafts, the test shafts with the grips attached were subjected to 24 hours of humidity aging, and the resulting adhesive grips were subjected to torque testing. Also tested were golf grips that had no composition applied to the interior (attached using only a solvent) and were not subjected to humidity aging, and golf grips that had no composition applied to the interior (attached using only a solvent) and were subjected to 24 hours of humidity aging.
[0062] Torque testing was performed using the same equipment and method outlined in Example 1. The grips tested were prepared according to Table 2 below.
[0063] [Table 2]
[0064] Grip F was prepared by applying a solvent (mineral spirits) to the shaft, not taping the shaft, and not applying an adhesive composition on the inner surface of the grip. Grip G was prepared by applying a solvent (mineral spirits) to the shaft, taping the shaft, and not applying an adhesive composition on the inner surface of the grip. Grip H was prepared by first dissolving polyisobutylene in mineral spirits to form an adhesive composition, applying the adhesive composition on the inner surface of the grip, allowing the adhesive composition to dry, and then applying a solvent (mineral spirits) to the shaft and not taping the shaft. Grip I was prepared in the same manner as Grip H, except that the adhesive composition was prepared by dissolving C5 resin in mineral spirits. Each of Grips F-I was attached using mineral spirits.
[0065] After Grip F was mounted on the test mandrel, it was allowed to dry at room temperature for at least 4 hours to dry the applied composition and set the grip on the test mandrel.After Grips G-I were mounted on the test mandrel, they were subjected to humidity aging at 32° C. and 95% relative humidity for 24 hours.
[0066] FIG. 7 shows the results of the angle (measured in degrees of deflection) data obtained from torque testing of the formulations in Table 2. The performance of Grip F represents the control baseline, while Grip G performs close to the control baseline. Also shown is the historical performance of a typical golf grip that was conventionally installed using tape and solvent. In this example, both Grips H and I performed above the baseline (i.e., experienced more slip / deflection / rotation when torque was applied), but Grip I was much closer to the baseline than Grip H.
[0067] Example 3
[0068] In Example 3, an adhesive composition containing 10 parts C5 resin (the adhesive composition described above for Grips C and I) was further tested and applied to four grips attached to a test shaft, each using a different solvent. The resulting adhesive grips were subjected to torque testing. Golf grips without any composition applied to the interior ("blow": attached using compressed air) and golf grips without any composition applied to the interior (attached using solvent only; one of these grips included application of double-sided tape) were also tested. Both grips that were dried at room temperature for 24 hours and grips that were humidity aged for 24 hours under the conditions described in Example 2 were tested.
[0069] Torque testing was performed using the same equipment and method outlined in Example 1. The grips tested were prepared according to Table 3 below.
[0070] [Table 3]
[0071] Grip J1 was prepared by applying a solvent (mineral spirits) to the shaft, taping the shaft, and applying no adhesive composition to the inside surface of the grip. Grip J2 was prepared by applying a solvent (mineral spirits) to the shaft, taping the shaft, and applying no adhesive composition to the inside surface of the grip. Grips K1 and K2 were each prepared by first dissolving C5 resin in mineral spirits to form an adhesive composition, applying the adhesive composition onto the inner surface of the grip, allowing the adhesive composition to dry, and then using compressed air to blow the grip onto the shaft without taping the shaft. Grips L1 and L2 were each prepared by first dissolving C5 resin in mineral spirits to form an adhesive composition, applying the adhesive composition onto the inner surface of the grip, allowing the adhesive composition to dry, and then applying a solvent (mineral spirits) to the shaft without taping the shaft. Grips M1 and M2 were prepared in the same manner as grips L1 and L2, except that the solvent applied was water. Grips N1 and N2 were prepared in the same manner as grips L1 and L2, except that the solvent applied was acetone. An example of acetone may be obtained from Sherwin-Williams Canada, Inc. (180 Brunel Road, Mississauga, Ontario, Canada). Grips O1 and O2 were prepared in the same manner as Grips L1 and L2, except that the solvent used was naphtha, an example of which is available from Sherwin-Williams Canada, Inc. (180 Brunel Road, Mississauga, Ontario, Canada).
[0072] After grips J1 and J2 were mounted on the test mandrel, they were allowed to sit at room temperature for approximately 4 hours. After grips K1, L1, M1, N1, and O1 were mounted on the test mandrel, they were allowed to dry at room temperature for 24 hours. After grips K2, L2, M2, N2, and O2 were mounted on the test mandrel, they were subjected to 24 hours of humidity aging as described above.
[0073] Table 4 below provides angle (measured in degrees of deflection) data results from torque testing of the formulations in Table 3. The data shows that when compared to the control baseline data without 10 parts C5 resin and with tape, the deflection data for any of the test solvents subjected to room temperature drying was up to 28% lower than the control, and the deflection data for any of the test solvents subjected to humidity aging was up to 32% lower than the control. When compared to the control baseline data without 10 parts C5 resin and with tape, the deflection data for any of the test solvents subjected to room temperature drying was up to 16% lower than the control, and the deflection data for any of the test solvents subjected to humidity aging was up to 21% lower than the control. All were below 4.5 degrees, including the control group.
[0074] [Table 4]
[0075] Example 4
[0076] In Example 4, four different compositions were applied to golf grips, a solvent was applied, the grips were attached to test shafts, the test shafts with the attached grips were subjected to 72 hours of humidity aging, and the resulting adhesive grips were subjected to torque testing.
[0077] Torque testing was performed using the same equipment and method outlined in Example 1. The grips tested were prepared according to Table 5 below.
[0078] [Table 5]
[0079] Grips P, Q, and R were prepared by first dissolving both polyisobutylene and C5 resin in mineral spirits (according to the composition listed in Table 5) to form an adhesive composition, applying the adhesive composition onto the inner surface of the grip, allowing the adhesive composition to dry, and then applying a solvent (mineral spirits) to the shaft without taping the shaft. Grip S was prepared in the same manner as Grip P, except the adhesive composition was prepared by dissolving only the listed amount of polyisobutylene in mineral spirits.
[0080] After grips P-S were mounted / installed onto the test mandrel, they were subjected to humidity aging at 32° C. and 95% relative humidity for 72 hours.
[0081] FIG. 8 shows the results of the angle (measured in degrees of deflection) data obtained from torque testing of the formulations in Table 5. Also shown is the historical performance of a typical golf grip that was conventionally installed using tape and solvent. Grips P, Q, and S performed above baseline in this example (i.e., experienced more slip / deflection / rotation when torque was applied). Grip R performed nearly at baseline.
[0082] Example 5
[0083] In Example 5, the four compositions of the grips in Table 5 above were used as sample materials (in this example, the sample materials were supplied by Unit 1&2 Ltd., Market Square, Peterborough, PE6 8EQ, United Kingdom). The adhesive composition was applied to a clean, level, flat, horizontal surface of a clean piece of sample material (this is the same compound as the Tour Velvet golf grip by EATON Golf Pride® available from The Stirling Centre, Northfields Road, Deeping) and the resulting prepared samples were subjected to an adhesion test to measure the tack or "stickiness" of the adhesive composition after drying. Application of the composition to the sample material involved using a plastic pipette to place up to 1 mL of the composition on a flat, horizontal surface on top of a clean piece of sample material (in this example the sample was 2 inches long and 2 inches wide).
[0084] Compositions P, Q and R were prepared by first dissolving both the polyisobutylene and C5 resin (according to the composition in Table 5 above) in mineral spirits to form an adhesive composition, applying the adhesive composition onto a flat surface of a sample material, and allowing the adhesive composition to dry for 72 hours. Composition S was prepared in the same manner as composition P, except that the adhesive composition was prepared by dissolving only the polyisobutylene in the amount listed in mineral spirits.
[0085] Each prepared sample was allowed to dry at room temperature for 72 hours. The test equipment used was a Mark-10® Force Tester, Model M5-50 and a Mark-10® Stand, Model ESM303, both available from Mark-10, Inc. (11 Dickson Avenue, Copiague, NY 11726). The prepared and dried sample was mounted on a horizontal metal platform with the adhesive composition side facing up, and the underside of the sample (opposite the adhesive) was applied with double-sided tape to secure the prepared sample to the platform. A stainless steel fixture (having a circular flat surface with a diameter of 12.5 mm) connected to the force tester was lowered along the stand at a rate of 5 inches per minute, so that the flat surface of the fixture was in contact with the adhesive composition on the prepared sample. The fixture was lowered until a force of 20 Newtons was applied, and then the fixture was left on the surface for 10 seconds. The fixture was then pulled upward at a rate of 20 inches per minute. The programs for the downward movement, force application, hold time, and upward movement were automated into the test apparatus and therefore repeatable.
[0086] The Mark-10 instrument measures the maximum applied force, the compound relaxation force after a hold time, and the tack number. The tack number (measured in grams force (gF)) corresponds to the force required to pull the sensor of the test instrument away from the adhesive surface of the prepared sample. A higher tack number indicates a greater tackiness / stickiness of the adhesive composition (which may contribute to a stronger adhesion of the grip to the shaft) and is therefore desirable.
[0087] Figure 9 shows the Tack Number (measured in gF) data results from adhesion testing of the compositions in Table 5. Composition P performed exhibited negligible adhesion. Composition R performed exhibited the highest amount of tack.
[0088] Although specific embodiments have been described herein, the scope of the technology is not limited to those specific embodiments. Those skilled in the art will recognize other embodiments or modifications that are within the scope of the technology. However, Accordingly, specific structures, acts, or operations are disclosed as example embodiments only. The scope of the technology is defined by the following claims and any equivalents therein. Accordingly, specific structures, acts, or operations are disclosed as example embodiments only. The scope of the technology is defined by the following claims and any equivalents therein. Examples of the disclosure may be described according to the following embodiments.
[0089] Mode 1. A method of coating a grip with an adhesive composition, comprising the steps of preparing the adhesive composition, wherein preparing the adhesive composition comprises dissolving at least one adhesive in a solvent, applying the adhesive composition onto an inner surface of a grip, and allowing the adhesive composition to dry for a predetermined period of time.
[0090] Aspect 2. The method of aspect 1, wherein the ratio of the at least one adhesive to the solvent is 1 to 10.
[0091] Aspect 3. The method of aspect 1, wherein the at least one adhesive is selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
[0092] Embodiment 4. The method of embodiment 3, wherein the at least one adhesive comprises polyisobutylene.
[0093] Aspect 5. The method of aspect 1, further comprising dissolving a second adhesive in the solvent.
[0094] Aspect 6. The method of aspect 5, wherein the ratio of the solvent to the second adhesive is 10 to 1.
[0095] Aspect 7. The method of aspect 5, wherein the second adhesive is selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
[0096] Example 8. The method of example 7, wherein the at least one adhesive comprises polyisobutylene and the second adhesive comprises a C5 resin.
[0097] Example 9. The method of example 8, wherein the ratio of polyisobutylene to C5 is 1 to 1.
[0098] Aspect 10. The method of any one of the preceding aspects, wherein the solvent comprises mineral spirits.
[0099] Aspect 11. The method of any of the preceding aspects, wherein the grip is a golf club grip.
[0100] Aspect 12. The method of aspect 1, further comprising the steps of applying a second solvent onto the outer surface of the shaft, sliding the inner surface of the grip over the outer surface of the shaft, wherein the second solvent acts as a lubricant on the shaft, and allowing the second solvent to dry, wherein the adhesive composition adheres the grip onto the outer surface of the shaft.
[0101] Aspect 13. The method of aspect 12, further comprising the steps of removing the grip from the shaft, applying the second solvent onto an outer surface of the end of the shaft, sliding an inner surface of a second grip onto the outer surface of the shaft, where the second grip includes the adhesive composition on the inner surface of the second grip and the second solvent acts as a lubricant on the shaft, and allowing the second solvent to dry, whereby the adhesive composition adheres the second grip onto the outer surface of the shaft. The method described.
[0102] Aspect 14. The method of any one of aspects 12-13, wherein the second solvent is selected from the group consisting of mineral spirits, acetone, water, and naphtha.
[0103] Aspect 15. The method of any one of aspects 12 to 13, wherein the second solvent comprises the same solvent as the first solvent.
[0104] Aspect 16 The method of any one of aspects 12-13, wherein the second solvent comprises a different solvent than the first solvent.
[0105] Aspect 17. A method comprising the steps of applying a solvent onto an outer surface of a shaft, sliding an inner surface of a grip over the outer surface of the shaft, wherein the solvent acts as a lubricant on the shaft and the grip comprises an adhesive composition on the inner surface of the grip, and allowing the solvent to dry, causing the adhesive composition to adhere the grip onto the outer surface of the shaft.
[0106] Aspect 18. The method of aspect 17, wherein the solvent is selected from the group consisting of mineral spirits, acetone, water, and naphtha.
[0107] Aspect 19. The method of aspect 17, wherein the adhesive composition comprises at least one adhesive selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
[0108] Aspect 20. The method of aspect 17, further comprising the steps of removing a grip from the shaft, applying the second solvent onto the outer surface of the end of the shaft, sliding the inner surface of a second grip over the outer surface of the shaft, wherein the second grip includes the adhesive composition on the inner surface of the second grip, the second solvent acting as a lubricant on the shaft, and allowing the second solvent to dry, wherein the adhesive composition adheres the second grip onto the outer surface of the shaft.
[0109] Aspect 21. A kit for attaching a grip to a shaft, comprising: a grip; and a solvent, wherein the grip defines an inner surface configured to fit onto the outer surface of the end of the shaft, the grip comprises a coating of an adhesive composition on the inner surface of the grip, and the adhesive composition comprises at least one adhesive, and wherein the solvent, when applied onto the outer surface of the end of the shaft, provides lubrication for attaching the inner surface of the grip onto the outer surface of the end of the shaft, and wherein the adhesive adheres the grip to the shaft when the inner surface of the grip is attached onto the outer surface of the end of the shaft.
[0110] Aspect 22. The method of aspect 21, wherein the solvent is selected from the group consisting of mineral spirits, acetone, water, and naphtha.
[0111] Aspect 23. The method of aspect 21, wherein the adhesive composition comprises at least one adhesive selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
[0112] 24. A golf club grip, comprising: a grip, the grip including a body, the body enclosing an interior volume; an inner surface of the body, the inner surface defining the interior volume; and an adhesive film coated on the inner surface of the body, the adhesive film comprising at least one including adhesive;including golf club grip.
[0113] Aspect 25. The method of aspect 24, wherein the adhesive composition comprises at least one adhesive selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
[0114] 26. An adhesive composition for application on an inner surface of a grip, comprising: about 0 to 10 parts C5 resin, about 2.5 to 10 parts polyisobutylene, and A composition comprising about 100 parts solvent.
[0115] Aspect 27. The composition of aspect 26, wherein the solvent comprises mineral spirits.
[0116] About 10 parts C5 resin, about 2.5 parts polyisobutylene, and 27. The composition of embodiment 26, further comprising about 100 parts of a solvent.
[0117] Embodiment 29. The composition of embodiment 26, further comprising about 10 parts C5 resin, about 5 parts polyisobutylene, and about 100 parts solvent.
[0118] Embodiment 30. The composition of embodiment 26, further comprising about 10 parts C5 resin, about 10 parts polyisobutylene, and about 100 parts solvent.
[0119] Aspect 31. The composition of aspect 26, further comprising about 10 parts polyisobutylene, and about 100 parts solvent.
[0120] While preferred embodiments and implementations of the present disclosure have been described, modifications and equivalents of the disclosed concepts may readily occur to those skilled in the art, however such modifications and equivalents are intended to be included within the scope of the claims appended hereto.
[0121] For purposes of this application, directional terms such as "top," "bottom," "upper," and "lower" are intended to be described with respect to the above disclosure and, where applicable, with respect to the orientations shown in the figures for clarity. Examples embodied and included in the claims may include examples in which the systems and devices are in different orientations.
[0122] Although specific applications of the present technology have been shown and described above, the disclosed technology can be used in a variety of environments, according to many examples of the present technology. The above discussion is not meant to suggest that the disclosed technology is only suitable for implementation in the environments shown and described above. As will be understood, the various aspects described with respect to the figures herein are not intended to limit the present technology to the specific aspects described. Thus, additional configurations can be used to implement the technology described herein and / or some aspects described can be excluded without departing from the methods and systems disclosed herein.
[0123] This disclosure describes several aspects of the technology with reference to the accompanying drawings, illustrating only some of the possible aspects. However, other aspects may be embodied in many different forms and should not be construed as being limited to the aspects set forth herein. Rather, these aspects are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the possible aspects to those skilled in the art.
[0124] Similarly, where process operations are disclosed, those operations are described for purposes of illustrating the present technology and are not intended to limit the disclosure to a particular order of operations. Without being limiting, operations may be performed in a different order, two or more operations may be performed simultaneously, additional operations may be performed, and disclosed operations may be omitted. Further, each operation may be accomplished via one or more sub-operations. The disclosed processes may be repeated.
Claims
1. 1. A method for coating a grip with an adhesive composition, comprising: preparing the adhesive composition, wherein the step of preparing the adhesive composition comprises dissolving at least one adhesive in a solvent; applying the adhesive composition onto an inner surface of the grip; and Allowing the adhesive composition to dry for a predetermined period of time; The method includes:
2. The method of claim 1 , wherein the ratio of said at least one adhesive to said solvent is 1 to 10.
3. The method of claim 1 , wherein the at least one adhesive is selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
4. The method of claim 3 , wherein the at least one adhesive comprises polyisobutylene.
5. The method of claim 1 further comprising dissolving a second adhesive in the solvent.
6. The method of claim 5 , wherein the ratio of said solvent to said second adhesive is 10 to 1.
7. The method of claim 5 , wherein the second adhesive is selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
8. The method of claim 7, wherein the at least one adhesive comprises polyisobutylene and the second adhesive comprises a C5 resin.
9. 9. The method of claim 8, wherein the ratio of polyisobutylene to C5 is 1 to 1.
10. 10. The method of any one of claims 1 to 9, wherein the solvent comprises mineral spirits.
11. The method of any one of claims 1 to 10, wherein the grip is a golf club grip.
12. applying a second solvent onto the exterior surface of the shaft; sliding the inner surface of the grip over the outer surface of the shaft, wherein the second solvent acts as a lubricant on the shaft; and allowing the second solvent to dry, wherein the adhesive composition adheres the grip onto the exterior surface of the shaft; The method of claim 1 further comprising:
13. removing the grip from the shaft; applying the second solvent onto an exterior surface of the end of the shaft; sliding an inner surface of a second grip over an outer surface of the shaft, wherein the second grip includes the adhesive composition on the inner surface of the second grip and the second solvent acts as a lubricant on the shaft; and allowing the second solvent to dry, wherein the adhesive composition adheres the second grip onto the exterior surface of the shaft; The method of claim 12 further comprising:
14. 14. The method of any one of claims 12-13, wherein the second solvent is selected from the group consisting of mineral spirits, acetone, water, and naphtha.
15. 14. The method of any one of claims 12 to 13, wherein the second solvent comprises the same solvent as the first solvent.
16. 14. The method of any one of claims 12 to 13, wherein the second solvent comprises a different solvent than the first solvent.
17. applying a solvent onto an exterior surface of the shaft; sliding an inner surface of a grip over an outer surface of the shaft, where the solvent acts as a lubricant on the shaft and the grip includes an adhesive composition on the inner surface of the grip; and allowing the solvent to dry and causing the adhesive composition to adhere the grip onto the exterior surface of the shaft; The method includes:
18. 18. The method of claim 17, wherein the solvent is selected from the group consisting of mineral spirits, acetone, water, and naphtha.
19. 20. The method of claim 17, wherein the adhesive composition comprises at least one adhesive selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
20. removing the grip from the shaft; applying the second solvent onto an exterior surface of the end of the shaft; sliding an inner surface of a second grip over an outer surface of the shaft, wherein the second grip includes the adhesive composition on the inner surface of the second grip and the second solvent acts as a lubricant on the shaft; and allowing the second solvent to dry, wherein the adhesive composition adheres the second grip onto the exterior surface of the shaft; 20. The method of claim 17, further comprising:
21. A kit for attaching a grip to a shaft, comprising: A grip and a solvent, wherein the grip defines an inner surface configured to fit over an outer surface of an end of the shaft, the grip includes a coating of the adhesive composition on the inner surface of the grip, and the adhesive composition includes at least one adhesive; and wherein when the solvent is applied onto the outer surface of the end of the shaft, the solvent provides lubrication for mounting the inner surface of the grip onto the outer surface of the end of the shaft, and when the inner surface of the grip is mounted onto the outer surface of the end of the shaft, the adhesive adheres the grip to the shaft. kit.
22. 22. The method of claim 21, wherein the solvent is selected from the group consisting of mineral spirits, acetone, water, and naphtha.
23. 22. The method of claim 21, wherein the adhesive composition comprises at least one adhesive selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
24. A golf club grip, a grip, the grip including a body, the body enclosing an interior volume; an interior surface of the body, the interior surface defining an interior volume; an adhesive film coated on the inner surface of the body, wherein the adhesive film comprises at least one adhesive; Including golf club grips.
25. 25. The method of claim 24, wherein the adhesive composition comprises at least one adhesive selected from the group consisting of polyisobutylene, C5 resin, and alkylphenol resin.
26. 1. An adhesive composition for application onto an inner surface of a grip, comprising: C5 resin about 0 parts to 10 parts, about 2.5 parts to about 10 parts polyisobutylene, and Solvent: about 100 parts, A composition comprising:
27. 27. The composition of claim 26, wherein the solvent comprises mineral spirits.
28. Approximately 10 parts of C5 resin, about 2.5 parts polyisobutylene, and Solvent: about 100 parts, 27. The composition of claim 26, further comprising:
29. Approximately 10 parts of C5 resin, about 5 parts polyisobutylene, and Solvent: about 100 parts, 27. The composition of claim 26, further comprising:
30. Approximately 10 parts of C5 resin, about 10 parts polyisobutylene, and Solvent: about 100 parts, 27. The composition of claim 26, further comprising:
31. about 10 parts polyisobutylene, and Solvent: about 100 parts, 27. The composition of claim 26, further comprising: